2009
DOI: 10.2478/s11756-009-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Water repellency of post-boggy soils with a various content of organic matter

Abstract: The objective of this study was to estimate the water repellency of post-boggy soils in north-eastern Poland. Potential water repellency was determined based on the water drop penetration time (WDPT) test and the molarity of an ethanol droplet (MED) test. A total of 276 soil samples with a varied organic carbon (OC) content, ranging from trace amounts in sandy subsoils to 44.4% in organic soils, were analyzed. The investigated material represents peat-muck soils (Eutri-Sapric Histsols) and muck-like soils (Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
(24 reference statements)
1
15
1
Order By: Relevance
“…It is thought that irreversible drying of organic matter is one of the main causes of water repellency of soil (Lachacz et al, 2009), which is particularly important in drained peatlands as they can no longer fulfill the role of a "sponge" for water. However, the time the soil needs to absorb water varies greatly, which has been noted in previous studies (Lachacz et al, 2009;Orzechowski et al, 2013). It should also be noted that we investigated the potential water repellency in air-dried soil samples at the sites that were differently influenced by the moorsh-forming processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that irreversible drying of organic matter is one of the main causes of water repellency of soil (Lachacz et al, 2009), which is particularly important in drained peatlands as they can no longer fulfill the role of a "sponge" for water. However, the time the soil needs to absorb water varies greatly, which has been noted in previous studies (Lachacz et al, 2009;Orzechowski et al, 2013). It should also be noted that we investigated the potential water repellency in air-dried soil samples at the sites that were differently influenced by the moorsh-forming processes.…”
Section: Discussionmentioning
confidence: 99%
“…Kořenková et al, 2015). It was shown (e.g., Blanco-Canqui and Lal, 2009;Goebel et al, 2008;Lachacz et al, 2009;Vogelmann et al, 2013) that soil water sorptivity decreased exponentially with increasing SOM content. Czachor et al (2013), Leelamanie and Karube (2007), Vogelmann et al (2013), and Woche et al, (2005) also reported a non-linear increase of the contact angle with SOM content.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of SWR in mineral soils has been relatively well documented (Jordán et al , ), whereas SWR in peat soils has been studied less often. Research by Berglund & Persson (), Lachacz et al (), Orzechowski et al () & Hewelke () investigated factors influencing SWR in peat (organic), and Szatylowicz et al () examined spatial and temporal moisture variations in peat. These studies indicate that peat SWR depends on the SMC but can also strongly affect the soil moisture distribution.…”
Section: Introductionmentioning
confidence: 99%